Surprise on the day of judgment in Matthew 25:31-46 and The Book of the Watchers - Njeri, George (Neotestamentica, 2020)
In Matthew 25:31-46, Jesus describes the final judgment of humankind in apocalyptic terms, and as in other apocalyptic texts the righteous are rewarded and the wicked are punished. Yet in Matthew’s final judgment both the righteous and the wicked are surprised at their status and completely unaware of the criteria for judgment. Although “surprise” is usually noted with regard to the timing of the eschaton, it is an element that has otherwise been neglected in studies of apocalyptic. Are the wicked always unaware of their misdeeds? Are the righteous not usually self-righteous? Comparison with The Book of the Watchers (1 Enoch 1-36) demonstrates that for Enoch the Watchers know they did wrong, but they are nonetheless disappointed that Enoch cannot intervene to help them before God. Matthew plays much more on the idea of complete surprise in paradoxically encouraging his community to do good without realising it.